Does the introduction of pre‐operative cardiopulmonary exercise testing in radical cystectomy delay or alter surgical care?. Issue 3 (12th December 2021) - Lockhart, Kathleen R.; Carroll, Rosemary; Tiu, Albert; Blatt, Alison
Abstract: Objectives: To assess if the introduction of routine pre‐operative cardiopulmonary exercise testing (CPET) in radical cystectomy has delayed surgical intervention. Materials and Methods: A prospective database of patients undergoing radical cystectomy in our local health network was maintained. A retrospective analysis of two years (2018–2020) included 38 patients. Of these, 15 patients had CPET pre‐operatively, and a direct comparison was performed. Results: The mean time from diagnosis to cystectomy was 95 days in patients who did not have CPET compared to 110 days for those who did ( p  = 0.32), with comparable rates of neoadjuvant chemotherapy (NAC) (62.5% and 64.29%). Average length of stay was 18.6 days compared with 13.87 ( p  = 0.16), favouring the CPET group. The CPET group also had a lower readmission rate within 30 days (13.33% compared with 21.05%, p  = 0.35). Cause‐specific mortality within 90 days was 10.2% and within the study timeframe was 36.84% (estimated 5‐year mortality rate 43–65%). Within the CPET group, eight had an anaerobic threshold (AT) of <11 ml/kg/min (range 6.3–10.5): Of these, 50% had Clavien‐Dindo complications of grade 2 or higher and the 90‐day mortality rate was 37.5% (cf. 0% in those with AT > 11 ml/kg/min in this series). Conclusion: CPET is a valuable risk evaluation tool. This study suggested that CPET contributed to a minor non‐significant delay to surgery, however was associated with reduced length of stay and readmission rates, and was a valuable risk evaluation tool. We found that CPET AT <11 ml/kg/min is associated with higher rates of patient morbidity and perioperative mortality.